2006
DOI: 10.1089/ten.2006.12.3055
|View full text |Cite
|
Sign up to set email alerts
|

In VitroMicrodistraction of Preosteoblasts: Distraction Promotes Proliferation and Oscillation Promotes Differentiation

Abstract: Osteoblast biology is influenced in vivo by a 3-dimensional (3D) extracellular matrix that mediates their adhesion and interaction and by a constant state of compressive and tensile forces. To study the role of mechanical stress on osteoblasts in vitro, these parameters must be addressed. Therefore, this study describes the use of a novel, in vitro system that subjects cells to distractive and compressive forces in a 3D environment. This system, termed a microdistractor system, was used to apply linear forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…OC/ BGLAP, the most abundant protein in bone, is a mature osteoblastic marker and its expression correlates with bone formation (Bilezikian et al, 2002;Ferna´ndez-TresguerresHerna´ndez-Gil et al, 2006;Hall, 2005). Up-regulation of OC/Bglap expression has been reported under cyclic tensile strain after 9 days (Mikuni-Takagaki et al, 1996) and upregulation of Akp2 and OC/Bglap was shown under periodic distraction and compression of collagen type I gels after 8 days (Gabbay et al, 2006). However, OC/Bglap expression has not been shown to be up-regulated by mechanical strain in other studies (Kaspar et al, 2000;Koike et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…OC/ BGLAP, the most abundant protein in bone, is a mature osteoblastic marker and its expression correlates with bone formation (Bilezikian et al, 2002;Ferna´ndez-TresguerresHerna´ndez-Gil et al, 2006;Hall, 2005). Up-regulation of OC/Bglap expression has been reported under cyclic tensile strain after 9 days (Mikuni-Takagaki et al, 1996) and upregulation of Akp2 and OC/Bglap was shown under periodic distraction and compression of collagen type I gels after 8 days (Gabbay et al, 2006). However, OC/Bglap expression has not been shown to be up-regulated by mechanical strain in other studies (Kaspar et al, 2000;Koike et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, studies used 3-D culture systems to observe the effects of biomechanical forces on osteoblastic cells (Cartmell et al, 2003;Duty et al, 2007;Gabbay et al, 2006;Tanaka et al, 2005). Other studies observed cell growth in 3-D cultures in the absence of any mechanical stimuli (Cao et al, 2003;Ishaug et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loboa et al found that regions exposed to tensile strains of 13% or less corresponded to bone regeneration, whereas low periosteal hydrostatic pressures were associated with cartilaginous differentiation. In efforts to further dissect the influence of mechanical forces on osteogenesis at a cellular level in vitro, Gabbay et al used a microdistraction device capable of applying linear forces in a three-dimensional environment (39). MC3T3 preosteoblasts were suspended in three-dimensional collagen gels and exposed to either continuous distraction, or cyclical distraction and compression.…”
Section: Distraction Osteogenesismentioning
confidence: 99%
“…The response of osteoblasts to mechanical signaling is attributed to deformation of the cell and surrounding matrix [2] [3]. Previous studies have shown that compressive loading induces mineralization of osteoblastic cells [4] and is an effective up-regulator of osteogenesis [5]. Furthermore, static and dynamic compression of chondrocytes has been shown to effect the regulation of type II collagen and aggrecan gene expression [6].…”
Section: Introductionmentioning
confidence: 99%